The role of variation and plasticity in parental care during the adaptive radiation of three‐spine sticklebacks. (25th March 2019) - Stein, Laura R.; Bell, Alison M.
Abstract: Phenotypic plasticity might influence evolutionary processes such as adaptive radiations. Plasticity in parental care might be especially effective in facilitating adaptive radiations if it allows populations to persist in novel environments. Here, we test the hypothesis that behavioral plasticity by parents in response to predation risk facilitated the adaptive radiation of three‐spine sticklebacks. We compared the behavior of fathers across multiple ancestral (marine) and derived (freshwater) stickleback populations that differ in time since establishment. We measured behavioral plasticity in fathers in response to a predator found only in freshwater environments, simulating conditions marine males experience when colonizing freshwater. The antipredator behavior of males from newly established freshwater populations was intermediate between marine populations and well‐established freshwater populations. In contrast to our predictions, on average, there was greater behavioral plasticity in derived freshwater populations than in ancestral marine populations. However, we found greater individual variation in behavioral reaction norms in marine populations compared to well‐established freshwater populations, with newly established freshwater populations intermediate. This suggests that standing variation in behavioral reaction norms within ancestral populations might provide different evolutionary trajectories, and illustrates how plasticity can contribute to adaptive radiations.